Gonad development, gonad index and condition index of marsh clam Polymesoda epansa Mousson from Miri, Malaysia - Abdul Rahim, Azimah (2014)
The research study was conducted at Kelulit mangrove, Sibuti, Miri from October 2010 until November 2011. Monthly sampling has been done by recording and collecting data and samples from the study area. Further analysis for histological studies and condition index were brought to the laboratory at UPM Bintulu Campus. The IUCN Red list has stated Polymesoda expansa as a least concern. Thus, little information is available on P. expansa found in Sarawak especially on the reproductive cycle. The aim of this research study was to conduct histological investigations that lead to explain the dynamics of gonad development, gonad index, and condition index of P. expansa at Miri, Sarawak. Study on the gametogenesis of P. expansa from Miri, Sarawak was performed using histological sections. Several steps involved in the processes including dissection, fixation, dehydration, clearing, infiltration with paraffin wax, embedding in paraffin wax, sectioning, staining and mounting. Microscopic observations of gonad sections determine that P. expansa was dioecious species. Five (5) stages of gonad development has been carried out and clearly identified for both male and female which includes rest, development, mature, spawn and spent. The rest phase in P. expansa in this study was observed only in the months of January, May June and October. On the other hand, development, mature spawning and spent phases were observed throughout the study period. Thus, active and continuous gametogenesis was recorded throughout the study period since the tropical conditions are fairly stable throughout the year. In the determination of gonad index (GI), the same sample population was used. Sixty nine (69) individuals were prepared for histological analysis. GI was figured by following a numerical grading system in order to obtain a quantitative value that represents the reproductive activity. The GI calculation was (the numbers in each stage) x (numerical ranking of that stage) / (number of animals in the samples). The values for pooled of P. expansa were higher in November 2010 and November 2011 with the value of 2.3 and 2.8, and were lower in December 2010, June and September 2011 with the value of 1.5 and 1.0. The GI values indicated that the reproduction was inactive in December, June and September while gametogenesis started in January and continued until July. GI has shown a seasonal trend along the year with high values related with mature individuals while the fall of GI values due to spawning activity. Spawning between sexes was fairly synchronized except in January, and September. Between March and July, spawning activities was occurred mainly in males but it shown less in September. However, no significant differences (p>0.05) of GI was found between males and females since spawning activities were all year around. Condition index (CI) of P. expansa was concurrently studied with the histological observations. Fifty five (55) specimens were processed in the size range of 65-75 mm due to the average of collected samples. CI that was generally used to characterize the physiological activity of organisms was calculated by [dry tissue weight (g) / (dry shell weight (g) x 100]. The values varied from 1.8% in December 2010 to 3.4% in October 2011, which could be categorized as thin to moderate. In present study, the CI showed a clear relationship with the reproductive cycle (gametogenesis). The close correlation between condition index and gonad development indicated that condition index is a good indicator for identifying the gonad maturity of P. expansa.